2011
DOI: 10.1111/j.1399-0012.2010.01315.x
|View full text |Cite
|
Sign up to set email alerts
|

The University Worksite Organ Donation Project: a comparison of two types of worksite campaigns on the willingness to donate

Abstract: To test the impact of different campaign strategies, a year-long campaign was conducted to promote organ donation among university faculty, staff, and students. Two universities were assigned to each of three conditions: a media-only campaign, a mass media-plus-interpersonal outreach condition, and a control condition. Universities were counter-balanced by geographic region and diversity of population. Changes from pretest to post-test on the key-dependent measures, including signing a donor card and discussin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…Previous findings have shown that mass media-plus-interpersonal media has a greater impact on behavior, especially about signing donor card [46]. In our study, interpersonal media had a positive significant effect on the participants' knowledge.…”
Section: Resultssupporting
confidence: 56%
“…Previous findings have shown that mass media-plus-interpersonal media has a greater impact on behavior, especially about signing donor card [46]. In our study, interpersonal media had a positive significant effect on the participants' knowledge.…”
Section: Resultssupporting
confidence: 56%
“…The analysis yielded 3 groups 1 : first with most successful interventions (N ¼ 62), 7,8,17,24,25,32 second with successful interventions (N ¼ 20), 9,10,18,19,20,[26][27][28][29][30]34,[11][12][13][14][15][16] and third with least successful interventions (N ¼ 10). [21][22][23]29,31,33,35,36 The first group of studies shown in Table 2 consisted of most successful interventions (N ¼ 6) that used more SMBC (mean ¼ 4.17) and have set and achieved 3 to 4 goals with 100% success rate. The dominant intervention approach in this group was the educational approach.…”
Section: Success Of Interventions In Correlation With the Use Of Smbcmentioning
confidence: 99%
“…Studies investigating factors associated with the likelihood to register as a donor and effective interventions to increase registrations have shown that minority groups are generally less willing to donate but that multifaceted approaches that include mass media campaigns, point-of-decision interventions and interpersonal interventions increase registrations. [23][24][25][26][27] Interestingly, an astounding proliferation of donor registries has occurred in the US since 2006, with the total number of registrants increasing from approximately 60 million to 100 million people. 28 In addition, in all 50 states, an individual's designation as a registered donor is now honored with no further requirement for family authorization.…”
Section: Donor Registrationsmentioning
confidence: 99%